PTH-111 The Impact of Rifaximin-Alpha on NHS Hospital Resource Use in UK Patients with Hepatic Encephalopathy: A Retrospective Observational Study (Impress). (17th August 2016) - Aspinall, R; Radwan, A; Shaya, G; Sodatonou, H; Cipelli, R; Hudson, M
Abstract : Introduction: In clinical trials rifaximin-α (RFX) has been shown to reduce the risk of an overt episode of hepatic encephalopathy (HE) and the number of HE-related hospitalisations, but there are limited data describing its impact on healthcare resource use in real world UK practice. This study compared hospital resource use pre- and post-RFX initiation in UK patients. Methods: A retrospective observational study in 11 specialist National Health Service (NHS) centres of 145 patients prescribed RFX for HE between July 2008 and May 2014. Local clinical staff reviewed patients' medical records for demographics, RFX prescribing and adverse drug reactions (ADRs) to RFX. Details of inpatient hospitalisations and hospital visits in the 12 months pre- and post-RFX initiation were extracted from NHS Trust electronic databases. Ethics reference 14/WS/1017. Results: Of the 145 patients evaluated, 89 (61%) were male. At RFX initiation, mean age was 61 years (standard deviation [SD] =11), 119 patients (82%) were on lactulose. Child-Pugh score was recorded for 67 (46%) patients (10% Class A, 54% B, 36% C). Resource use in the 6/12 months pre- and post-RFX initiation is shown in Table 1 ; to avoid non-survivor confounding this analysis includes the 114 patients (78%) who were alive at 6 months and 102 (70%) alive at 12 months post-RFX initiation. 3 patients (2%) had ADRs and 4 (3%) developed C.difficile infection (none of whom discontinued treatment). Conclusion: In UK clinical practice, treatment with RFX for HE is well-tolerated and associated with significant reductions in hospitalisation frequency, bed occupancy (including critical care) and emergency room visits; reductions are observed within 6 months of treatment initiation and sustained at 12 months. This is the first study to demonstrate a reduction in critical care bed occupancy with RFX. Disclosure of Interest: R. Aspinall Consultant for: Norgine. Consultant/UK advisory board member, A. Radwan Employee of: Norgine, G. Shaya Employee of: Norgine, H. Sodatonou Employee of: Norgine, R. Cipelli Consultant for: Norgine. Employee of pH Associates which was commissioned by Norgine Pharmaceuticals to provide support with study design and management, data analysis and scientific editorial services, M. Hudson Consultant for: Norgine. Attended advisory board and has given sponsored lectures (national or international) on behalf of Norgine.